AB0136 Clinical Aspects and Pathogenicity of Anti-Cyclic Citrullinated Glucose-6-Phospate Isomerase Peptide (CCG) Antibodies in Patients with Rheumatoid Arthritis. (10th June 2014) - Umeda, N.; Matsumoto, I.; Inoue, A.; Tanaka, Y.; Takai, C.; Kurashima, Y.; Kondo, Y.; Tsuboi, H.; Ogishima, H.; Suzuki, T.; Sumida, T.
Abstract : Background: Anti-citrullinated protein antibodies (Abs) (ACPA) have been reported as a hallmark of diagnosis and disease progression in sera of patients with rheumatoid arthritis (RA). Although several ACPA targeting citrullinated fibrinogen, collagen type II, alpha-enolase and vimentin have been confirmed, their pathogenic roles are still elusive. The Abs against glucose-6-phosphate isomerase (GPI) provoke spontaneous arthritis in K/BxN models. We previously demonstrated that anti-cyclic citrullinated GPI peptide (CCG) Abs were specifically upregulated in patients with RA and were linked to disease activity. However, the reason has not been clarified so far. Objectives: To elucidate the pathogenicity of anti-CCG Abs in patients with RA. Methods: 1) Anti-CCG-2, -4, -7 and citrullinated alpha-enolase-1 peptide (CEP-1) Abs were measured by ELISA in RA patients treated with infliximab (n=46) or tocilizumab (n=45). The levels of Abs were compared before and after six month treatment. Disease activity was evaluated by the disease activity score (DAS)-28 CRP. 2) The expression of citrullinated proteins were examined by immunochemical staining using anti-modified citrulline (AMC) Abs, which were kindly provided from Dr. Maruyama (Tokyo Metropolitan Institute of Gerontology), in RA and OA synoviums. 3) Anti-CCG-7 and CEP-1 Abs were purified from RA serum using peptide-affinity column. The deposition of anti-CCG-7 and CEP-1 Abs was examined by immunofluorescence staining in RA and OA synoviums. Results: 1) Treatment with infliximab significantly reduced the levels of anti-CCG-2 and -7 Abs (P<0.001, P<0.01, respectively). Treatment with tocilizumab significantly reduced the levels of anti-CCG-4 and -7 Abs (P<0.05, P<0.01, respectively), but not of anti-CEP-1 Abs. In each group, the mean value of the DAS-28 CRP decreased significantly after the treatment. 2) Citrullinated protein was specifically detected by anti-AMC Abs in the surface layer of RA synovium. 3) Affinity purified anti-CCG-7 and CEP-1 Abs were specifically deposited in their cytoplasm of RA synovium. Conclusions: Treatment with infliximab or tocilizumab downregulates anti-CCG-2, -4 and -7 Abs, and this effect seems to be linked to disease activity. Anti-CCG Abs could be considered as markers for disease activity in patients with RA. Our results suggested that several ACPA recognized citrullinated protein in the surface layer of RA synovium. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2649